Correlation between Demographic Information and Rate of Conflict among Nurses in Emergency Department - Ganji Zadeh, Mohsen; Mirbagher Ajorpaz, Neda; Naderi, Manijeh; Zagheri Tafreshi, Mansoureh (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: The conflict phenomenon has been always problematic in the health system leading to reduced efficiency of the staff and increased health care costs. Conflicts in the hospital are high due to frequent interactions among nurses, physicians, and other members of the treatment team and their multiple roles. This study expunged upon the correlation between demographic information and the rate of conflict among the nurses in the emergency department (ED). Methods: A total of 147 nurses of teaching hospitals affiliated to Shahid Beheshti University of Medical Sciences participated in this descriptive-analytic study in October, 2015. The nurses were selected using the random cluster sampling method. The data were collected with a researcher-made instrument. The gleaned data were analyzed with descriptive statistics, Pearson product moment correlation coefficient, and one-way ANOVA. Results: Our findings demonstrated that the rate of conflict was higher in the intrapersonal dimension in nurses employed in ED of the hospitals under study compared to the other two dimensions, i.e., intraclass and interclass. There was significant correlation between gender and rate of conflict in intrapersonal and interclass dimensions while the rate of conflict was higher among the males than females. There was also a significant association between the rate of conflict in intraclass dimension and employment status. Conclusions: The results of this study can help managers to remove or diminish conflict-inducer factors. They may further adopt appropriate methods to manage conflict and promote nursing services through cooperative and supportive interaction.